The Chekhovian Intertext : Dialogue with a Classic - Parts, Lyudmila (Book collections on Project MUSE., 2008)
"In The Chekhovian Intertext, Lyudmila Parts explores contemporary Russian writers' intertextual engagement with Chekhov and his myth. She offers a new interpretive framework to explain the role Chekhov and other classical writers play in constructing and maintaining Russian national identity and the reasons for the surge in the number of intertextual engagements with the classical authors during the cultural crisis in post-perestroika Russia." "The book highlights the intersection of three distinct concepts: cultural memory, cultural myth, and intertextuality. It is precisely their interrelation that explains how intertextuality came to function as a defense mechanism of culture, a reaction of cultural memory to the threat of its disintegrant." "In addition to offering close readings of some of the most significant short stories by contemporary Russian authors and by Chekhov, as a theoretical case study the book sheds light on important processes in contemporary literature: it explores the function of intertextuality in the development of Russian literature, especially post-Soviet literature; it singles out the main themes in contemporary literature and explains their ties to national cultural myths and to cultural memory. The Chekhovian Intertext may serve as a theoretical model and impetus for examinations of other national literatures from the point of view of the relationship between intertextuality and cultural memory."--Jacket